Instrumentalising the digital: adolescents' engagement with ICTs in low- and middle-income countries. Issue 3 (3rd April 2018) - Banaji, Shakuntala; Livingstone, Sonia; Nandi, Anulekha; Stoilova, Mariya
ABSTRACT: In development agendas regarding children in low-income communities, both older and emerging media are typically ignored or assumed to have beneficial powers that will redress social and gender inequality. This article builds on a recent rapid evidence review on adolescents' digital media use and development interventions in low- and middle-income countries to examine the contexts of children and adolescents' access to, and uses of, information and communication technology(ICT). Noting that only a handful of studies heed the significance of social class and gender as major axes of inequality for adolescents, the article scrutinises the gap between the rhetoric of ICT-based empowerment and the realities of ICT-based practice. It calls for a radical rethinking of childhood and development in light of the actual experiences, struggles, and contexts.